2022
DOI: 10.1213/ane.0000000000005919
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Versus General Anesthesia for Cesarean Delivery in Pregnant Women With Moyamoya Disease: A Retrospective Observational Study

Abstract: BACKGROUND: Moyamoya disease, a rare chronic cerebrovascular disease with a fragile vascular network at the base of the brain, can cause ischemic or hemorrhagic strokes or seizures. Precise blood pressure control and adequate analgesia are important for patients with moyamoya disease to prevent neurological events such as ischemia and hemorrhage. This study aimed to compare the intraoperative mean arterial pressure of pregnant women with moyamoya disease according to the mode of anesthesia (general anesthesia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Moreover, sympathetic blockade gives rise to the vasodilation as well as a decrease in cardiac output [29]. RA averts hypertension caused by tracheal intubation or extubation [34]. Meanwhile, studies have shown that RA in hip fracture surgery is capable of lessening the need for perioperative blood transfusion [23,35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sympathetic blockade gives rise to the vasodilation as well as a decrease in cardiac output [29]. RA averts hypertension caused by tracheal intubation or extubation [34]. Meanwhile, studies have shown that RA in hip fracture surgery is capable of lessening the need for perioperative blood transfusion [23,35].…”
Section: Discussionmentioning
confidence: 99%